CONTEMPORARY DRIFTS IN DIABETES MANAGEMENT - SARKAR, SHRUBAWATI; SADHU, SOUMOK; ROY, RUPAK; TARAFDAR, SAMBIT; MUKHERJEE, NABANITA; SIL, MOUMITA; GOSWAMI, ARUNAVA; MADHU, NITHAR RANJAN (International Journal of Applied Pharmaceutics, 2023)
Diabetes mellitus is a cumulative effect of various cellular and biochemical malfunctions which trigger the blood glucose level far beyond the normal range. From 1980 to 2014, more than 314 million individuals had diabetes. Epidemiology states that it is becoming more prevalent in low-income, middle-income, more specifically, third-world countries than the first-world countries. It showed mortality rate increased by 5% in premature ages. It was the 9th leading reason for almost 1.5 million deaths. The diagnosis clearly suggests the replacement of insulin-producing pancreatic endocrine cells. Stem cell treatment substitutes the infected or destroyed cells from pluripotent stem cells or multipotent stem cells. One of the favourite ways to understand and treat diabetes mellitus is embryonic stem cells, including pluripotent cells. The in vitro demonstration of iPSC-derived pancreatic cells for treating infection is a grizzled dream of scientists. Luckily, iPSC-derived cells combat the major problems that arose in this field and still, there are no legal and ethical bindings as well as immunological rejections. Later, the β cell of the pancreas has derived from PSCs from various patients who have diabetes. The study proves there is a wide possibility of demonstrating and rectification of clinical administration of these newly developing trends. The use of stem cell therapy in vitro, which is explicit patient research, shows various concerns related to the pathophysiology of diabetes. Successful application of procedures of screening of the apoptosis of β-cells from inbuilt cell retrieval needed to be a proper arrangement of new cell lines.